Incidence of Cleft Lip and Palate in Erbil City (Mustansiria Dental Journal, 2018)
Aims: This study was conducted to assess the epidemiology and some of the possiblerisk factors causing cleft lip and palate in Erbil city.Materials and Methods: the data were obtained from the records of Raparinpaediatric and maternity hospital in the center of Erbil city. The file records oflive births during a period from January 2000 to January 2008 were reviewed forthe occurrence of cleft lip and palate. The cleft cases were evaluated for site andtype of cleft and sex of the infant. and some risk factors.Results: 121 cleft lip and/or palate cases out of 60418 live births were registered. Theoverall incidence was 2:1000 live births. The percentage of cleft lip and palate,cleft palate only, cleft lip only was 55%, 30%, and 15% respectively. The ratioswith respect of left or right or bilateral cleft was approximately 4.5:2:1.The infantsex and site of family residence showed no significant influence on the incidenceof clefting. Maternal age of more than 30 years, maternal smoking, and positivefamily history of clefts, consanguineous marriage and low infant birth weightsignificantly increased the incidence of cleft lip and palate. About 7.4% of cleftcases were associated with other congenital anomalies, most frequentlycongenital heart disease.Conclusion: The incidence of cleft lip and/or cleft palate is 2:1000 births. Theincidence of cleft lip and palate is two times greater than cleft palate alone, andthree times than cleft lip alone. Cleft lip was two times greater on the left sidethan on the right side. The incidence of clefts was greater in males than females.